Are more prescriptive laws better? Transforming REDD+ safeguards into national legislation - Ituarte-Lima, C; McDermott, C (Oxford University Press, 2017)
International schemes for financing conservation and climate mitigation, such as Reducing Emissions from Deforestation and Degradation and forest enhancement (REDD+), have generated concerns about the effect of large influxes of money on good governance, the human rights of local land users, and biodiversity. While there is agreement on the need for safeguards to prevent negative effects, how prescriptive or flexible those safeguards should be is not well understood. We develop a framework for a multi-scale comparison of the prescriptiveness of measures to reduce carbon emissions with safeguards for community rights and biodiversity, and apply this framework to international REDD+ safeguards and their transformation into Mexican law. Our findings reveal significant differences across substantive and procedural safeguards with positive and negative impacts on community rights. We also find that not prescribing ownership over forest carbon and de-bundling property rights from rights to benefit from ecosystems stewardship, helped overcome political conflicts in Mexico and enhanced the potential for equity in REDD+ outcomes.